KETERSEDIAAN NITROGEN AKIBAT PEMBERIAN BERBAGAI JENIS KOMPOS PADA TIGA JENIS TANAH DAN EFEKNYA TERHADAP PERTUMBUHAN TANAMAN JAGUNG (Zea mays L.) - Novalinda Barus; Muhammad Majid Damanik; Supriadi Supriadi (Jurnal Agroekoteknologi, 2013)
The aim of this research was study the effect of soil types and compost to provide nutrients nitrogen and growth of corn plant. Nitrogen is an essential nutrient by the main source of organic material from corn required with high levels at the age of four weeks to optimum product in soils low levels of nitrogen. For it has done a research in the field screen Agriculture Faculty University of Sumatera Utara (± 25 m above sea level) in June-August 2012 by using a factorial Randomized Block Design in two factors: types of soils were entisols, inceptisol and ultisol and compost were control, straw compost + chicken manure, straw compost + cocoa fod compost, cocoa fod compost + chicken manure. Parameters measured were soil pH, soil C-organic, soil N-total, ratio of C/N soil, plant height, plant dry weight, N plant level and N-plant uptake.The results showed that the combination of various organic matter on the three soil types significantly affect to the C-organic, N-total soil, plant height, plant dry weight and N-plant uptake.